Exports, Margins and Productivity Growth: With an Application to the Canadian Softwood Lumber Industry - Bernstein, Jeffrey I. (The Review of Economics and Statistics, 1994)
Jeffrey I. Bernstein, Exports, Margins and Productivity Growth: With an Application to the Canadian Softwood Lumber Industry, The Review of Economics and Statistics, Vol. 76, No. 2 (May, 1994), pp. 291-301